Comparison of the Force-, Velocity-, and Power-Time Curves Between the Concentric-Only and Eccentric-Concentric Bench Press Exercises. Issue 6 (June 2020) - Pérez-Castilla, Alejandro; Comfort, Paul; McMahon, John J.; Pestaña-Melero, Francisco L.; García-Ramos, Amador
Abstract : Abstract: Pérez-Castilla, A, Comfort, P, McMahon, JJ, Pestaña-Melero, FL, and García-Ramos, A. Comparison of the force-, velocity-, and power-time curves between the concentric-only and eccentric-concentric bench press exercises. J Strength Cond Res 34(6): 1618–1624, 2020—The aim of this study was to compare the temporal and mechanical variables between the concentric-only and eccentric-concentric bench press (BP) variants. Twenty-one men (age: 22.0 ± 4.2 years, body mass: 73.4 ± 7.7 kg, height: 177.2 ± 8.0 cm; 1 repetition maximum [1RM]: 1.12 ± 0.12 kg·kg −1 ) were evaluated during the concentric-only and eccentric-concentric BP variants using 80% 1RM. Temporal (concentric phase duration, propulsive phase duration, and time to reach the maximum values of force, velocity, and power) and mechanical variables (force, velocity, and power), determined using a linear velocity transducer, were compared between both BP variants. All temporal variables were significantly lower during the eccentric-concentric BP compared with the concentric-only BP ( p ⩽ 0.05; effect size [ES] range: 0.80–2.52). Maximum force as well as the mean values of velocity and power were significantly higher for the eccentric-concentric BP compared with the concentric-only BP (all p < 0.001; ES range: 2.87–3.58). However, trivial to small differences between both BP variants were observed for mean force (ES: 0.00–0.36) as well as for maximum velocity (ES: 0.40) and power (ES: 0.41). The stretch-shortening cycle (i.e., eccentric-concentric BP) mainly enhanced force production at the early portion of the concentric phase, but this potentiation effect gradually reduced over the latter part of the movement. Finally, force was higher for the concentric-only BP during 49% of the concentric phase duration. These results suggest that both BP variants should be included during resistance training programs to optimize force output at different points of the concentric phase.